2009
DOI: 10.1109/jstsp.2008.2011104
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of Head and Neck Lymph Node Regions for Radiotherapy Planning Using Active Contour-Based Atlas Registration

Abstract: Abstract-In this paper, we present the segmentation of the head and neck lymph node regions using a new active contour-based atlas registration model. We propose to segment the lymph node regions without directly including them in the atlas registration process; instead, they are segmented using the dense deformation field computed from the registration of the atlas structures with distinct boundaries. This approach results in robust and accurate segmentation of the lymph node regions even in the presence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 27 publications
1
48
0
Order By: Relevance
“…In the work of Gorthi et al 4 CT images are of similar size ͑0.9375 mmϫ 0.9375 mmϫ 3 mm͒ and the sensitivity, DSC, and Hausdorff distance are reported. In their leave-one-out experiment, the mean DSC reported for levels IIA, IIB, III, and IV are 0.53, 0.46, 0.43, and 0.36, respectively, while the mean DSC for our ASM-based segmentation is 0.698 for levels II-IV segmented as a single structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work of Gorthi et al 4 CT images are of similar size ͑0.9375 mmϫ 0.9375 mmϫ 3 mm͒ and the sensitivity, DSC, and Hausdorff distance are reported. In their leave-one-out experiment, the mean DSC reported for levels IIA, IIB, III, and IV are 0.53, 0.46, 0.43, and 0.36, respectively, while the mean DSC for our ASM-based segmentation is 0.698 for levels II-IV segmented as a single structure.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative validation performed in this study showed an improvement in specificity compared to a standard atlas-based method as well as a reduction in sensitivity. Gorthi et al 4 also used an atlas-based approach, but the deformation was computed with structures easily visible in the images ͑bones, trachea, and skin͒ and then applied to the rest of the image. This led to relatively large ͑14.52-21.81 mm͒ segmentation errors for the average Hausdorff distance for node levels II-IV.…”
Section: Introductionmentioning
confidence: 99%
“…Many works about lymph node segmentation in CT images have been developed. [33][34][35][36][37][38][39][40][41] In this work, using the centroids of lymph node candidates as seed points [ Fig. 8(a) a level-set-based curve evolution is applied [ Fig.…”
Section: D False Positive Rejectionmentioning
confidence: 99%
“…The ground truth segmentations are performed by a medical expert, under the supervision of a radiation oncologist. In Gorthi et al (2009), we used a preliminary version of the current framework with the main focus being the specific H&N lymph nodes segmentation problem. We now perform a detailed evaluation with the current framework, and also study the effect of combining various registration forces in an hierarchical manner for this application.…”
Section: Segmentation Of Head and Neck Lymph Nodesmentioning
confidence: 99%